2021
DOI: 10.1021/acschembio.1c00157
|View full text |Cite
|
Sign up to set email alerts
|

Synthase-Selective Exploration of a Tunicate Microbiome by Activity-Guided Single-Cell Genomics

Abstract: While thousands of environmental metagenomes have been mined for the presence of novel biosynthetic gene clusters, such computational predictions do not provide evidence of their in vivo biosynthetic functionality. Using a fluorescent in situ enzyme assay targeting carrier proteins common to polyketide (PKS) and non-ribosomal peptide synthetases (NRPS), we applied fluorescence-activated cell sorting to tunicate microbiome to enrich for microbes with active secondary metabolic capabilities. Single-cell genomics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…D. californiensis as a putative PKS/NRPS active cell. To date, our studies have focused on the use of the KC-12 probe based on its ability to label carrier proteins (CP) associated with fatty acid (ACPs), polyketide (ACPs), and NRPS (PCPs) synthesis [ 47 ]. As shown schematically in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…D. californiensis as a putative PKS/NRPS active cell. To date, our studies have focused on the use of the KC-12 probe based on its ability to label carrier proteins (CP) associated with fatty acid (ACPs), polyketide (ACPs), and NRPS (PCPs) synthesis [ 47 ]. As shown schematically in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the probe KC-12 hijacks coenzyme A (CoA) biosynthesis in cells to produce a fluorescently-labeled analog of coenzyme A (Fig. 1 a) [ 46 , 47 ]. This fluorescently labeled CoA can be post-translationally added to the active site serine residue on acyl-carrier proteins (ACP) and peptidyl-carrier proteins (PCPs) associated with PKS and NRPS, respectively [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pipeline can be a one-stop, high-throughput system based on microfluidics. Recently, a single-cell analysis method linking metabolic and genomic features has been developed based on labeling of synth(et)ase enzymes ( 39 ). The potential advantage of MERMAID is the detection of various types of intracellular biomolecules with specific molecular features.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy was applied to extract an enriched fraction of the tunicate microbiome actively expressing bioactive compounds at the time of sampling. Through fluorescent labelling of the carrier proteins involved in NRP and PK biosynthesis and subsequent fluorescence activated cell sorting (FACS), it was possible to enrich the BGC content from 0.77 to 1.17 BGC per Mbp [97] .…”
Section: Tapping Into Microbial Biosynthetic Diversitymentioning
confidence: 99%